Cross-adaptive polarity switching strategies for optimization of audio mixes - Pestana, Pedro Duarte (2016)
Crest factor is an often overlooked part of audio production, yet it acts as an important limit to overall loudness. We propose a technique to optimize relative polarities in order to yield the lowest possible peak value. We suggest this is a way of addressing loudness maximization that is more sonically transparent than peak limiting or compression. We also explore additional uses that polarity analysis may have in the context of mixing audio. Results show this is a fairly e ective strategy, with average crest factor reductions of 3 dB, resulting in equivalent values for loudness enhancement. While still not comparable to the amount of reduction peak limiters are typically used for, the approach is seen as more transparent via subjective evaluation, through a multi-stimulus test.